Characteristics of Nitric Acid‐Modified Carbon Nanotubes and Desalination Performance in Capacitive Deionization. Issue 9 (8th August 2018) - Bao, Shenxu; Duan, Jihua; Zhang, Yimin
Abstract: Multiwalled carbon nanotubes (MWCNTs) were treated by nitric acid to probe the effect of nitric acid modification on their properties and desalination performance in capacitive deionization (CDI). The nitric acid modification exerts a slight influence on the morphologies, specific surface area, and pore properties of the MWCNTs but can increase the amount of oxygen‐containing functional groups and then obviously enhance the specific capacitance of the electrodes. Thus, the desalination efficiency can be significantly improved as the modified MWCNTs serve as electrodes in CDI. The adsorption of salt ions on the original and modified MWCNT electrode is fitted well by the Freundlich isotherm other than the Langmuir isotherm. Abstract : Capacitive deionization is an emerging charge‐based water desalination technology. In order to improve the electrochemical properties of the electrodes, multiwalled carbon nanotubes were treated with nitric acid to evaluate the effect of modification on their properties and desalination performance in capacitive deionization. The desalination efficiency could be largely improved by this treatment.